OPTIMALISASI POLA PENATAAN RUANG PADA PASAR TRADISIONAL GEMPOLKEREP, KABUPATEN MOJOKERTO - Faizah Choirunnisa; Azkia Avenzoar (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: This research is motivated by the condition of Pasar Gempolkerep which affects the productivity of buying and selling transaction activities in it which has an impact on the economy of Gempolkerep Village and its surroundings. The muddy conditions, the irregular position of the traders' kiosks, the location of the market at the entrance to the village make the face of the village look shabby and the buying and selling transactions in it are uncomfortable and irregular. These problems occur due to the confusion of the spatial division zone. Article 28 I paragraph (3) and Article 32 paragraph (1) of the 1945 Constitution of the Republic of Indonesia explain that traditional markets are a reflection of local wisdom and part of Indonesian national culture that must be preserved. The existence of the market is very vital for the economic joints of Gempolkererep Village and its surroundings. Most residents depend on their economy on this village market. Because of its very vital function, the village government makes the management of this market a priority, including its arrangement. According to Ching (1996) spatial planning patterns are spatial arrangements that are related to each other according to function, proximity, or circulation flow so that they are organized into spatial patterns that are closely related to each other or coherent. If the spatial pattern or spatial zone is considered appropriate, then the productivity of the community engaged in activities in it will be guaranteed and of course this will have a positive impact on the economy of Gempolkerep Village and its surroundings. The purpose of this study is to evaluate the existing spatial pattern so that it can later produce the right spatial zone for Pasar Gempolkerep. This study uses a method with a qualitative category through location surveys and literature studies. From this study, it is hoped that the spatial zone of Pasar Gempolkerep will be organized so that the productivity of economic activities in it increases and creates better market conditions. Keyword: spatial pattern, traditional market, dry zone, wet zone Abstrak: Penelitian ini dilatar belakangi oleh kondisi pasar Gempolkerep yang mempengaruhi produktifitas kegiatan transaksi jual beli didalamnya yang mana berdampak pada ekonomi Desa Gempolkerep dan sekitarnya. Kondisi becek, tak teraturnya posisi kios pedagang, letak pasar pada jalan masuk desa menjadikan wajah desa menjadi kumuh serta transaksi jual beli didalamnya tidak nyaman dan tidak teratur. Permasalahan tersebut terjadi akibat rancunya zona pembagian ruang. Pasal 28 I ayat (3) dan pasal 32 ayat (1) UUD Republik Indonesia Tahun 1945 menjelaskan bahwa pasar tradisional merupakan gambaran kearifan lokal dan bagian dari kebudayaan nasional Indonesia yang harus dilestarikan. Keberadaan pasar sangat vital bagi sendi perekonomian Desa Gempolkererep dan sekitar. Sebagian besar warga menggantungkan perekonomiannya pada pasar desa ini. Karena fungsinya yang sangat vital maka pemerintah desa menjadikan pengelolaan pasar ini prioritas, termasuk segi penataannya. Menurut Ching (1996) pola tata ruang adalah susunan ruang yang memiliki kaitan satu dengan lainnya menurut fungsi, kedekatan, atau alur sirkulasi sehingga terorganisir menjadi pola – pola bentuk ruang yang berkaitan erat satu sama lain atau koheren. Apabila pola tata ruang atau zona ruang dinilai sudah tepat, maka produktifitas masyarakat yang berkegiatan di dalamnya akan terjamin dan tentu hal tersebut akan memberikan dampak positif bagi perekonomian Desa Gempolkerep dan sekitar. Tujuan diadakannya penelitian ini yaitu untuk mengevaluasi pola tata ruang yang ada agar nantinya dapat menghasilkan zona ruang yang tepat bagi Pasar Gempolkerep. Penelitian ini menggunakan metode dengan kategori kualitatif melalui survei lokasi dan studi literatur. Dari penelitian ini diharapkan zona ruang Pasar Gempolkerep tertata sehingga produktifitas kegiatan ekonomi di dalamnya meningkat dan menciptakan kondisi pasar lebih baik. Kata Kunci: pola tata ruang, pasar tradisional, zona kering, zona basah